2021
DOI: 10.52601/bpr.2021.210021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of <i>Streptococcus pyogenes</i> Cas9: a single-molecule perspective

Abstract: Cas9 is an RNA-guided endonuclease from the type II CRISPR-Cas system that employs RNA–DNA base pairing to target and cleave foreign DNA in bacteria. Due to its robust and programmable activity, Cas9 has been repurposed as a revolutionary technology for wide-ranging biological and medical applications. A comprehensive understanding of Cas9 mechanisms at the molecular level would aid in its better usage as a genome tool. Over the past few years, single-molecule techniques, such as fluorescence resonance energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…Our results also imply that these three main factors affect SpCas9 activity in a similar way. Former studies have shown that both the mismatches and the fidelity increasing mutations in eSpCas9 and SpCas9-HF1 loosely trap SpCas9 in a catalytically inactive intermediate state and slow down the transition of the HNH domain to the active state 24 , 36 40 . Mismatches, both PAM-proximal and PAM-distal when bona fide off-targets are engaged, inhibit the HNH domain transition and tend to keep the nuclease in this inactive state 38 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Our results also imply that these three main factors affect SpCas9 activity in a similar way. Former studies have shown that both the mismatches and the fidelity increasing mutations in eSpCas9 and SpCas9-HF1 loosely trap SpCas9 in a catalytically inactive intermediate state and slow down the transition of the HNH domain to the active state 24 , 36 40 . Mismatches, both PAM-proximal and PAM-distal when bona fide off-targets are engaged, inhibit the HNH domain transition and tend to keep the nuclease in this inactive state 38 42 .…”
Section: Resultsmentioning
confidence: 99%